Time Is Not Money: Income Is More Important Than Lifestage for Explaining Patterns of Residential Yard Plant Community Structure and Diversity in Baltimore - Avolio, Meghan; Blanchette, Allison; Sonti, Nancy F.; Locke, Dexter H. (Frontiers in Ecology and Evolution, 2020)
Plant biodiversity is affected by limiting resources such as water, nutrients, and sunlight. In urban settings, such as residential yards, however, limiting resources may also include the social factors of time and money spent on yard care. To examine the role that these precious human resources play in determining plant community structure and diversity, we surveyed homeowners and their yards in 12 neighborhoods across Baltimore City and Baltimore County, Maryland, visiting a total of 96 residential properties. We chose neighborhoods based on residents’ median income (a proxy for money) and lifestage (a proxy for time) as determined by ESRI’s Tapestry dataset (older [>65 and most likely retired with more free time] versus younger [<65 and most likely working with less free time]). At each residential yard, we studied four major plant types: lawn species, flowering herbaceous plants (excluding grasses), trees, and invasive species. For the flowering plants, we documented the number, size, and color of flowers, and calculated total floral area. We found that residential yards harbored high plant diversity with 89 tree species, 82 lawn species, and 80 flowering plant genera. Lawn richness was not related to the neighborhood-level lifestage of the residents or their income, rather, all lawns were equally weedy. Consistently, we found that yards in higher income neighborhoods and larger yards had greater abundance of plants and greater diversity of flowering herbaceous plants, trees and invasive species, whereas lifestage was rarely associated with plant diversity. Additionally, we found front yards had greater floral area than back yards, while back yards had greater tree abundance and tree diversity than front yards. Finally, we found that residents who spent more time doing yard work had more flowering plants, flower colors, and floral genera. Overall, yards in high-income neighborhood, and large yards had the greatest plant biodiversity, indicating that money is the more precious human resource for creating and maintaining biodiverse residential yards.